An Estimation of the Thermal Properties of Pu-Rich Metallic Fuel - Naoya Odaira; Yuji Arita (Advances in Materials Science and Engineering)
Pu-rich metallic fuel is promising for transuranic element burners. In this study, we calculated the thermal properties of Pu-rich metallic fuel. The thermal conductivity was calculated by using both Nordheim’s rule and Wiedemann–Franz law. The thermal conductivity of Pu-40Zr (14.3 Wm−1·K−1 at 600 K) was much lower than that of U-10Zr (23.5 Wm−1·K−1 at 600 K), another candidate metallic fuel. This addresses the metallic fuel has much lower durability in accidental situations than U-Zr metallic fuel. Thus, we also calculated thermal conductivity of the Pu-20U-20Zr alloy. The result shows uranium addition to the Pu-Zr alloy increased the thermal conductivity. In addition, we calculated the melting point of the Pu-(0–80U)-20Zr alloy and the result shows uranium addition increased melting point. This result suggests the accident tolerance of the Pu-rich metallic fuel increases by adding uranium.